2013
DOI: 10.5946/ce.2013.46.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Recent Update of Gastrointestinal Endoscope Reprocessing

Abstract: As infection-related issues have become one of the most important concerns in endoscopy centers, proper reprocessing of endoscopes has attracted great interest. Compliance with established guidelines for reprocessing is critical to prevent pathogen transmission. However, hospital compliance with guidelines has not been satisfactory. To increase compliance, efforts have focused on developing new and more innovative disinfectants and an automated endoscope reprocessor. Reprocessing must be performed by appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In a special issue of Clinical Endoscopy that was presented at the 48th Korean Society of Gastrointestinal Endoscopy (KSGE) seminar held in 2013, two review articles summarized the presentation on GI endoscope reprocessing. 13 14 KSGE established endoscope cleaning and disinfection guidelines in 1995, with the first revision made in 2009 and the second one in 2012. Lee et al 14 discussed the endoscopic reprocessing steps and the required equipment proposed in the second revised guidelines because the endoscope contacts the mucosa of the upper GI tract and is considered as a semicritical equipment.…”
Section: Awareness Of Disinfection In Clinical Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In a special issue of Clinical Endoscopy that was presented at the 48th Korean Society of Gastrointestinal Endoscopy (KSGE) seminar held in 2013, two review articles summarized the presentation on GI endoscope reprocessing. 13 14 KSGE established endoscope cleaning and disinfection guidelines in 1995, with the first revision made in 2009 and the second one in 2012. Lee et al 14 discussed the endoscopic reprocessing steps and the required equipment proposed in the second revised guidelines because the endoscope contacts the mucosa of the upper GI tract and is considered as a semicritical equipment.…”
Section: Awareness Of Disinfection In Clinical Endoscopymentioning
confidence: 99%
“…Compliance for the established reprocessing guidelines is most important for the prevention of possible pathogen transmission during endoscopy. 13 In order increase compliance, efforts have focused on developing disinfectants and automated endoscope reprocessors, which were introduced in order to replace the manual reprocessing steps as well as provide effective disinfection and reduction of exposure to hazardous chemicals. Personnel who are in charge of endoscope reprocessing should be well trained for the entire procedure.…”
Section: Awareness Of Disinfection In Clinical Endoscopymentioning
confidence: 99%
“…According to recent studies, variation in the adenoma detection rate, a quality-controlled marker for screening colonoscopy, is closely associated with not only interval colorectal cancer risk but also the lifetime benefits and costs of colorectal cancer screening [ 2 , 7 , 8 , 9 , 10 , 11 , 12 ]. Although adequate screening colonoscopy quality is essential, 25–48% of colonoscopy cases do not achieve adequate bowel preparation [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 3 4 5 6 7 In 1995, the Korean Society of Gastrointestinal Endoscopy (KSGE) developed cleaning and disinfection guidelines for GI endoscopes that were subsequently revised and republished in November 2009, August 2012, and March 2015. 8 However, real practices for endoscope reprocessing may differ among sites, and alterations to protocols and deviations from standard procedures may occur over time. 9 In addition, several studies reported a lack of compliance with established guidelines for endoscope reprocessing.…”
Section: Introductionmentioning
confidence: 99%